Diagnostic accuracy of tests for Helicobacter pylori in an Alaska Native population - Bruden, Dana L (Baishideng Publishing Group Co., Limited, 2011)
AIM: To evaluate the accuracy of two non-invasive tests in a population of Alaska Native persons. High rates of Helicobacter pylori (H. pylori) infection, H. pylori treatment failure, and gastric cancer in this population necessitate documentation of infection status at multiple time points over a patient’s life. METHODS: In 280 patients undergoing endoscopy, H. pylori was diagnosed by culture, histology, rapid urease test, (13)C urea breath test (UBT), and immunoglobulin G antibodies to H. pylori in serum. The performances of (13)C-UBT and antibody test were compared to a gold standard defined by a positive H. pylori test by culture or, in case of a negative culture result, by positive histology and a positive rapid urease test. RESULTS: The sensitivity and specificity of the (13)C-UBT were 93% and 88%, respectively, relative to the gold standard. The antibody test had an equivalent sensitivity of 93% with a reduced specificity of 68%. The false positive results for the antibody test were associated with previous treatment for an H. pylori infection [relative risk (RR) = 2.8]. High levels of antibodies to H. pylori were associated with chronic gastritis and male gender, while high scores in the (13)C-UBT test were associated with older age and with the H. pylori bacteria load on histological examination (RR = 4.4). CONCLUSION: The (13)C-UBT outperformed the antibody test for H. pylori and could be used when a non-invasive test is clinically necessary to document treatment outcome or when monitoring for reinfection.